Peran Sistem Informasi Akuntansi sebagai Instrumen Transparansi Keuangan di Perguruan Tinggi Swasta - Felmadefi, Renita; Astarani, Juanda; Yunita, Khristina; Dosinta, Nina Febriana (Worksheet : Jurnal Akuntansi, 2025)
Financial transparency has become a critical governance issue for private higher education institutions (PHEIs) in Indonesia, where financial dependence on student tuition fees exposes weaknesses in accountability and legitimacy. This study explores the urgency of implementing an integrated Accounting Information System (AIS) as a strategic response to overcome manual financial reporting, data inconsistency, and information asymmetry between management and foundations. Adopting a qualitative case study approach, the research was conducted at a private higher education institution in Pontianak through in-depth interviews, documentation analysis, and observation. Data were analyzed using the Miles, Huberman, and Saldaña interactive model to identify patterns and theoretical linkages among stakeholders. The findings reveal that the absence of an integrated AIS leads to delays, reporting inaccuracies, and weak internal control, reflecting agency problems and limited adherence to good governance principles. From the perspectives of Agency Theory, Stakeholder Theory, and Good Governance Theory, AIS is not merely an administrative tool but a transformative governance instrument that strengthens transparency, accountability, and stakeholder trust. The study implies that digitalizing accounting systems in PHEIs is essential for reducing information asymmetry, improving institutional legitimacy, and advancing financial governance practices within Indonesia’s higher education sector.